Marketing Performance Studi Pada Inkubator Bisnis Universitas Sumatera Utara - Dirbawanto, Nana Dyki (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Today's marketing activities have turned to using information technology to address the challenge of marketing sustainability to get more out of resources while meeting greater expectations for building long-lasting relationships with customers. E-marketing capabilities represent business organizations to compete in the use of the internet and other information technologies to be able to facilitate effective and efficient interactions with customers. One of the emerging marketing is e-Marketing capability. The role of information technology helps business organizations to be able to carry out marketing capability activities online. Various organizational capabilities in managing electronic-based marketing are based on knowledge sharing by business organizations to improve marketing performance. The purpose of this study was conducted to see how much influence knowledge sharing and e-Marketing capability have on marketing performance. This type of research uses an explanatory with a quantitative approach with student respondents who have products marketed at the USU business incubator. The questionnaire was given to 100 respondents with a sampling technique, namely purposive sampling. The results showed that knowledge sharing cannot influence e-Marketing capability, knowledge sharing can influence marketing performance, and e-Marketing capability cannot influence marketing performance.